The Effect Of Diaphragmatic Breathing Exercise On Reducing Stress Levels In Adolescents With Telephysiotherapy Method - Siti Sundari; Dika Rizki Imania; Riska Risty Wardhani (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Background: Adolescents belong to an age group that often experiences psychological pressure. College students are adolescents who frequently feel stressed due to a heavy academic load (graduating on time), unmet expectations, a lack of self-control over various aspects of their lives, and the influence of their living environment. This study uses diaphragmatic breathing exercises to provide a relaxing and stabilizing effect on the nervous system, thereby reducing stress levels. Objective: This study aims to analyze the impact of diaphragmatic breathing exercises on reducing stress levels in the adolescent population through a telephysiotherapy approach. Method: This study used a quasi-experimental design and one-group pretest-posttest design. Participants were selected through a purposive sampling method, with a total of 20 individuals participating. The intervention protocol involved performing diaphragmatic breathing techniques twice a week over a four-week period. The measurement instrument used was the Perceived Stress Scale questionnaire. The data analysis procedure included descriptive normality testing, normality evaluation, and hypothesis testing. Results and Discussion: Hypothesis testing with the Wilcoxon test showed that the p-value was 0.001 (p<0.05), indicating a significant effect of the implementation of diaphragmatic breathing exercises in reducing adolescent stress levels through the telephysiotherapy method. Conclusion: The provision of diaphragmatic breathing exercises has an effect on reducing stress levels in adolescents.